2016
DOI: 10.1007/s13187-015-0978-x
|View full text |Cite
|
Sign up to set email alerts
|

Salud es Vida: a Cervical Cancer Screening Intervention for Rural Latina Immigrant Women

Abstract: Background This study examined the feasibility and efficacy of Salud Es Vida – a promotora-led, Spanish-language educational group session on cervical cancer screening (Pap tests), self-efficacy (belief in ability to schedule and complete a Pap test), and knowledge among immigrant Hispanic/Latina women from farmworker backgrounds. These women are disproportionately burdened with cervical cancer, with mortality rates significantly higher than non-Hispanic whites. Methods The two-arm, quasi-experimental study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(66 citation statements)
references
References 31 publications
1
60
0
5
Order By: Relevance
“…The results of the study are in accordance to a study by Lugue et al (2016) which concluded that self-efficacy is not related significantly to the behavior of using IVA screening. 5.…”
Section: The Influence Of Self-efficacy Tow-supporting
confidence: 89%
“…The results of the study are in accordance to a study by Lugue et al (2016) which concluded that self-efficacy is not related significantly to the behavior of using IVA screening. 5.…”
Section: The Influence Of Self-efficacy Tow-supporting
confidence: 89%
“…Skilled healthcare workers to intervene with different cultural backgrounds to better meet the migrants needs and encouraging medical doctors to promote CCS in appointments with migrant women may also play a role in increasing CCS participation. However, interventions aiming only to increase knowledge may be insufficient [64]. A multi-factor-oriented strategy can be a more effective approach to increase participation in CCS besides targeting individual-level factors or barriers.…”
Section: Discussionmentioning
confidence: 99%
“…While only 16% of participants were insured, many women knew they could receive low cost or free Pap tests at a local health department or free clinic and were also informed of these resources through our educational brochure. Moreover, because our study was in an urban area, there are more options for low-cost screening options and follow-up care than rural areas, where transportation barriers are more cumbersome and affordable healthcare options are more limited [6, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Our study also identified other factors besides insurance which were associated with not being up to date with screening such as not knowing where to go for screening, not having a regular provider, and psychosocial factors (e.g., attitudes toward screening results and self-efficacy)[31]. Self-efficacy is an important variable for intervention programs to target and measure changes to improve cervical cancer screening adherence [20, 6]. The participants in our study were able to identify free and low-cost providers to receive their Pap exams through family planning services at the health department for example.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation